MALAY LITERATURE: TRANSLATED OR NOT TO BE TRANSLATED - Mendrofa, Melania Priska (Elite Laboratory Jurusan Sastra Inggris Universitas Bangka Belitung, 2019)
In Asian literature, Malaysia is categorized as the minority for its literature. Its development in literary realm has just built for some decades. It is not like the other big countries, such as China, Japan, and many other Southeast Asia which have been famous for its literature in world. Having no difference with other literature, Malay literature is developed through translation. Since English is still the main language in world literature, Malay literature has to consider its literature to be translated in English too. Meanwhile, modern Malay literature has presented already the novels in form of English language verse. Many novelists have tendency to write directly in English rather than presenting their works in vernacular language (Malay language). Translation, specifically in English, does not play important role in Malay literature. Malay English novels can assist the circulation of Malay Literature around the world, yet it may also reduce the appreciation for Malay language itself. This paper aims to discuss Malay literature dilemma in using English as the vernacular language in novels or using English as the bridge for bringing Malay culture into World Literature.